A340 IDENTIFICATION OF A G4-QUADRUPLEX STRUCTURE MOTIF IN HEPATITIS B VIRUS GENOME: A POTENTIAL NOVEL DRUG TARGET. (1st March 2018) - Meier-Stephenson, V; Schultz, S; Coffin, C S; Patel, T
Abstract: Background: Approximately 240 million people worldwide are chronically infected with hepatitis B virus (HBV), one of the leading causes of liver cirrhosis and hepatocellular carcinoma (HCC). HBV persistence is due to the presence of its compact, stable, covalently closed circular DNA (cccDNA), which resides in the nucleus and acts as the template for all HBV mRNA transcripts. While current antiviral therapies are effective at viral suppression, they do not target HBV cccDNA and cannot eradicate infection, necessitating prolonged, if not lifelong therapy. The transcription of cccDNA is under the guidance of numerous host factors, which bind to the various promoter regions to aid the replication of HBV. In the pre-core promoter region, specifically, interrupting host-protein interaction via a single nucleotide mutation studies can abrogate the HBV production. Recently, we have found a unique structural motif in the pre-core promoter region—a G4-quadruplex—a distinct, stacked, four-guanosine folding arrangement of the DNA. Such quadruplexes are being discovered at key transcription and translation sites of numerous organisms and are thought to be important regulators of these processes. We hypothesize that the host proteins bind at the pre-core promoter site through a G4-quadruplex, and disruption of this inhibits binding, hindering replication. Aims: (1) Demonstrate that oligomers of the pre-core promoter region forms a quadruplex in its wildtype form; (2) Demonstrate that these motifs form in physiologically-relevant samples. Methods: The wild-type and single-nucleotide mutation oligomers of the pre-core binding region were solubilized and purified through FPLC. Fractions of the purified products underwent circular dichroism, electrophoretic mobility shift assay, and small angle X-ray scattering analyses. Next, a known quadruplex-binding protein, DHX36 was produced using an E.coli expression system with an added His-tag and purified using a cobalt bead column. Pull-down assays of the DHX36 with the two oligomers were performed. Finally, cccDNA was extracted from an HBV-infected explanted liver via the Hirt extraction method and a similar pull-down assay was performed. Results: Using several biophysical methods, we demonstrate that the wild-type oligomer forms quadruplex structures, while the mutant oligomer does not. As well, we show a known quadruplex-binding protein, DHX36 to bind only to the wild-type oligomer and provide evidence for an analogous in vitro process with cccDNA. Conclusions: This novel finding of a quadruplex in the pre-core region provides a unique opportunity to study a critical host-protein interaction in cccDNA transcription. Through the pursuit of high-resolution structural data, we will be creating the framework for designing a novel inhibitor of the resilient HBV cccDNA, the master template for HBV replication. Funding Agencies: Cumming School of Medicine Seed Grant, University of Calgary